Layered tin halide perovskites in photovoltaics - Zhu, Mengqiong; Chaudhary, Bhumika; Mishra, Anamika; Saliba, Michael; Milić, Jovana V. (Royal Society of Chemistry (RSC), 2026)
Tin-based halide perovskites are emerging as promising alternatives to traditional lead-based perovskites due to their lower bandgaps, decreased toxicity, and comparable chemical properties. These materials offer unique structural and functional benefits for optoelectronic applications and photovoltaics, particularly in their low-dimensional or layered (2D) forms. Recent advancements have improved the solar-to-electric power conversion efficiency of tin-based halide perovskites by relying on organic spacers to control crystallisation and stabilise the materials. The versatility of molecular compositions and structural tuning of layered tin halide perovskites makes them appealing for next-generation photovoltaic technologies. This review highlights the structural characteristics, synthetic methods, and properties of layered tin halide perovskites, providing a comprehensive overview and discussing future prospects for environmentally friendly perovskite photovoltaics.